Promoting the use of social-emotional learning in online teacher education - Noam Lapidot-Lefler (International Journal of Emotional Education, 2022)
The goal of this paper is to address the questions of how social-emotional learning [SEL] can be incorporated into online learning and what effect such integration can have on students. The COVID-19 outbreak significantly increased the use of online learning at all levels of education. However, research shows that the online learning experience may contribute to students’ feelings of distancing, alienation, and loneliness. The assumption underlying this study was that these negative feelings are not inherent to the online learning experience; rather, they can be avoided by using online-SEL (“O-SEL”) techniques that integrate SEL into online learning processes. This qualitative case study included 42 preservice teachers enrolled in a college of education in Israel, who participated in an online course that employed specific methods for integrating the SEL component. Analysis of students’ reactions to the course revealed that O-SEL not only improved students’ emotional experience but also enhanced their cognitive learning. These findings strongly suggest that models of online learning should include SEL. Additional research may confirm the positive O-SEL effects on students’ experience and achievements. In this context, the current study introduces the concept of “social-emotional presence,” which is necessary for learning and development to take place online.